Self-adhesive electrode applied to ZnO nanorod-based piezoelectric nanogenerators. (10th September 2019) - Yilmaz, Pelin; Greenwood, Peter; Meroni, Simone; Troughton, Joel; Novák, Petr; Li, Xuan; Watson, Trystan; Briscoe, Joe
Abstract: ZnO nanorod-based piezoelectric devices have gained wide attention in energy harvesting systems as they can be processed at low temperatures onto flexible plastic substrates, giving a good potential for low cost. However, the vacuum-evaporated, precious metal contacts remain a high-cost element of the devices. This paper discusses the use of transparent conductive adhesives (TCAs) as an alternative top contact that is free from both vacuum-evaporation and precious metals. TCA films of various thicknesses were tape-cast onto nickel microgrid on PET substrates and adhered using low-pressure cold-lamination to bond the adhesive component of the TCA to piezoelectric generators with the final device structure of PET/ITO/ZnO-seed/ZnO-nanorods/CuSCN/PEDOT:PSS/TCA. The piezoelectric performances of the devices were compared by measuring output voltage in open-circuit and maximum power output across a range of resistive loads. The voltage output was observed to rise with increasing TCA thickness, reaching a maximum value of 0.72 V generated with 110 μ m of TCA as top contact. However, the higher resistance due to increased TCA thickness led to decreased power output; a maximum calculated power of 0.25 μ W was obtained from the device with the thinnest TCA layer of 22 μ m. Finally, the performance of piezoelectric nanogenerators with TCA contacts were compared to a control device with an evaporated gold contact.